Jan y Julia cumplen anos - Rettich, Margret; Westphal, Catharina; Terzi, Marinella (Barcelona : Edebe, 2016)
Jan and Julia celebrate their birthday by throwing a party for their friends in which they share a birthday cake, play dress-up games, watch a puppet show, and enjoy other activities.
Keywords: Birthdays -- Fiction; Parties -- Fiction; Twins -- Fiction; Brothers and sisters -- Fiction; Family life -- Fiction; Spanish language materials